Modelling the Dispersion of Radionuclides in the Marine Environment An Introduction - Periánez, Raúl.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
This book is a practical guide to the subject of numerical modelling of radioactivity dispersion in the marine environment. Thus, the techniques and numerical procedures required are explained in detail, with the aim of enabling the reader to build a real mathematical model. The book covers basic concepts and techniques, such as solving the advection-diffusion equation in a simple 1D form, as well as the most recent developments (full 3D models for non-conservative radionuclides including chemical reactions and speciation). A chapter is dedicated to the basic hydrodynamic modelling that is always required to simulate the dispersion of tracers in the sea; Eulerian and Lagrangian modelling techniques are also described. A chapter describes sensitivity and uncertainty analysis, the final stage in modelling works. A review on some published radionuclide dispersion models is also included.
Model structure and processes -- to the transport equation -- Solving hydrodynamics -- Solving hydrodynamics and dispersion -- Modelling the dispersion of non conservative radionuclides -- Lagrangian dispersion models -- Dispersion in estuaries: an example -- Sensitivity analysis -- Review of some radionuclide dispersion models.
Keywords: Environmental sciences; Oceanography; Ecotoxicology; Sedimentology; Water pollution; Earth sciences; Math. Appl. in Environmental Science; Oceanography; Ecotoxicology; Sedimentology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Earth Sciences, general